Architecture design for soft errors - Mukherjee, Shubu (Amsterdam ; Boston : Morgan Kaufmann Publishers/Elsevier, 2008)
This book provides a comprehensive description of the architetural techniques to tackle the soft error problem. It covers the new methodologies for quantitative analysis of soft errors as well as novel, cost-effective architectural techniques to mitigate them. To provide readers with a better grasp of the broader problem deffinition and solution space, this book also delves into the physics of soft errors and reviews current circuit and software mitigation techniques. TABLE OF CONTENTS Chapter 1: Introduction Chapter 2: Device- and Circuit-Level Modeling, Measurement, and Mitigation Chapter 3: Architectural Vulnerability Analysis Chapter 4: Advanced Architectural Vulnerability Analysis Chapter 5: Error Coding Techniques Chapter 6: Fault Detection via Redundant Execution Chapter 7: Hardware Error Recovery Chapter 8: Software Detection and Recovery * Provides the methodologies necessary to quantify the effect of radiation-induced soft errors as well as state-of-the-art techniques to protect against them.
Device- and circuit-level modeling, measurement, and mitigation -- Architectural vulnerability analysis -- Advanced architectural vulnerability analysis -- Error coding techniques -- Fault detection via redundant execution -- Hardware error recovery -- Software detection and recovery.
Includes bibliographical references and index.
Keywords: Integrated circuits; Integrated circuits -- Effect of radiation on; Computer architecture; System design; Electronic books